INDONESIAN EFL STUDENTS' PERCEPTIONS AND CHALLENGES IN DEVELOPING ACADEMIC LISTENING COMPETENCE: A MIXED-METHOD INVESTIGATION - Deasy Yunita Siregar; Syakiroh Nadilla; Mutia Syahira Yulfiar; Juwita Rinda Rayani; Alvionita Gayatri; Afifah Arsyah (VISION, 2025)
This research examines how students perceive and understand academic listening, a fundamental skill for success in educational settings. Through questionnaire distribution among secondary and tertiary students, the study identifies common obstacles and approaches students employ when engaging with academic content. Findings reveal that although students acknowledge academic listening's significance, many encounter difficulties processing lecture structures, identifying key information, and maintaining focus during extended listening sessions. The restricted exposure to authentic academic discourse and insufficient training in specialized listening strategies compound these challenges. Recommendations include implementing systematic listening practice, enhancing exposure to genuine academic materials, and incorporating technology-based tools for autonomous skill development.